PROFESIONALISME GURU DALAM UPAYA MENINGKATKAN MUTU PEMBELAJARAN DI SEKOLAH MENENGAH PERTAMA NEGERI 19 PALU - Amir, Yusrawati (Katalogis, 2017)
Teachers’ professionalism is very dominant and important in formal education because, for the learnes, it becomes role model foe them. The succesful of education implementation is determined by teacher’s professionalism in providing the learners with learnibg activity. SMP Negeri 19 Palureveal that teachers’ preparing teaching instrument and media. This is shown by some teachers who got difficulties in developing learning process due to locking technology of learning. This research used qualitative method, in wich the data were analyzed data descriptively to describe the research result. It is found thet teachers’ professionalism in improving learning quality has not run well. The teachers lack competence in appllying teaching media. Lack creativity in managing leraning procces, and still get difficult in arranging appropriate lesson plan due to lock of treaning and insufficient facilities. Thus, teachers’ professionalism improvement be balanced with sustainable evaluation for the sake of identifying successful level of teaching output and improving a better education goal.